PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN DENGAN MENGGUNAKAN MEDIA APRON PADA ANAK USIA DINI KELOMPOK B TKIT NUSANTARA BANTEN - Sarwiti Sarwiti; Amat Hidayat; Siti Kholifah (Jurnal Anak Bangsa, 2023)
Knowing the concept of numbers is very important, because it is indirectly related to human daily life. In the introduction of the concept of numbers in group B it is still relatively lacking, which is marked by the lack of children's ability to say numbers in sequence, connecting number symbols with the number of objects. If learning the concept of numbers is given according to the child's abilities, then the child will have more control over the ability to recognize the concept of numbers. In learning to recognize the concept of numbers, it requires media that is attractive to children, one of which is the counting apron media. This study aims to improve the ability to recognize the concept of numbers in early childhood through the media of calculating aprons. This research method is classroom action research which refers to the Kemmis and Mc. Taggart includes four stages, namely (1) planning (2) action (3) observation (4) reflection. This research consists of 1 cycle, with 2 meetings. The data analysis technique used in this research is qualitative and quantitative data analysis. Data collection techniques using observation instruments, interviews, documentation, field notes and discussions. The results of this study stated that there was an increase in children's gross motor skills through traditional games, as evidenced by the average score of children's initial gross motor skills of 63.61% and the first cycle of 79.33%. The research findings that traditional games of cat and mouse can improve gross motor skills of TKIT Nusantara Banten children.